Technical Case Report of a Cranioplasty With ex vivo Frozen Ostoblastic Bone Graft From Large Skull Metastasis - Perng, Pang-Shuo; Lee, Po-Hsuan; Hsu, Hao-Hsiang; Huang, Chi-Chen; Huang, Chih-Yuan; Lee, Jung-Shun (Frontiers in Surgery, 2021)
Objective Liquid nitrogen cryotherapy has shown efficacy in the treatment of bone tumors of the extremities with good oncologic and functional outcomes. However, its application in metastatic skull tumors has been rarely reported and whether the adjuvant radiotherapy affects the future bone fusion is not yet explored. We report an immediate cranioplasty with the resected osteoblastic bone, which underwent ex vivo cryotherapy, and discuss the surgical techniques and postoperative images. Methods A 58-year-old man with esophageal adenocarcinoma, undergoing chemoradiotherapy, presented with a rapidly enlarging scalp mass for 5 months. Imaging revealed an enhancing mass, centered in the frontal skull bone with extracranial and intracranial invasion, suggestive of osteoblastic metastasis. After preoperative transarterial embolization, the tumor was excised en bloc. Immediate cranioplasty was performed with the osteoblastic bone graft after ex vivo cryotherapy. It was soaked in liquid nitrogen for 20 minutes, thawed at room temperature for 15 minutes, and soaked in povidone-iodine solution for 10 minutes. Then, the bone graft was fixed to its original place. Pathologic examination revealed metastasis originating from the esophagus. He underwent adjuvant radiotherapy for local tumor control. Results He had an uneventful clinical course without any neurologic deficit. Brain imaging during the six-month follow-up showed no tumor recurrence and partial bony union. Conclusions Cranioplasty using an autologous bone graft with ex vivo cryotherapy was helpful in the reconstruction of osteoblastic metastatic skull tumor treatment. It was a simple and cost-effective procedure that achieved satisfactory cosmetic results without negatively impacting bone fusion, even after adjuvant radiotherapy.